DESIGN OF ACCOUNTING RECORDING SYSTEM BASED ON MICROSOFT ACCESS AT KOKO KEI LAUNDRY - Ivone Ivone; Hendry Tinamo (Universitas Internasional Batam, 2022)
Koko Kei Laundry is a business that provides washing services located at Ruko Golden Land Blok K no 6, Batam. Koko Kei Laundry was chosen as a partner in carrying out Community Service (PkM) activities. Koko Kei Laundry has been using a simple recording system so that it cannot produce financial reports that comply with applicable standards. For the problems faced, the best solution in helping owners to produce financial reports is to create an accounting recording system based on Microsoft Access. The method used in data collection is done through interviews and direct observation to partner locations. The result of this service is to produce a computer-based accounting recording system suitable for the Laundry business so that the system can produce financial reports. The resulting financial statements consist of an income statement, a statement of financial position, a general ledger, and a sales report. The recording system created will be able to provide information that can make it easier for business owners when making decisions so that their business can sustain for a long time.